Of an Alien Homecoming : Reading Heidegger's Hölderlin. - Bambach, Charles R. (State University of New York Press, 2022)
The first book-length study in English of the Heidegger-Hölderlin relation, addressing the tension between Heidegger's political commitments during National Socialism and Hölderlin's ideal of poetic dwelling.
Keywords: Heidegger, Martin, -- 1889-1976.; Hölderlin, Friedrich, -- 1770-1843.; Heidegger, Martin, -- 1889-1976 -- Influence.; Hölderlin, Friedrich, -- 1770-1843 -- Influence.; Heidegger, Martin, -- 1889-1976; Hölderlin, Friedrich, -- 1770-1843; National socialism.; Political science -- Philosophy.; Nazisme.; National Socialism.; PHILOSOPHY / General.; Influence (Literary, artistic, etc.); National socialism; Political science -- Philosophy; Rezeption